On the issue of the activities of the executors as part of Kabardian provisional court in 1822-1858 - Georgy D. Ivanov (Кавказология, 2024)
The essay investigates the specifics of the executioners’ responsibilities in the Kabardian Provisional Court, which operated from 1822 until 1858. This topic has been investigated through reports, orders, communications, journal judgments of the temporary court, resolutions and inscriptions of higher authorities, and so on. The requirements for establishing the post of executor have been explored. The staff of the execution corps is described. Within the framework of this issue, attention is paid to: 1) standards for applicants for this position; 2) the procedure for selecting personnel for the position of executor; 3) personnel who ensure the activities of executors. The sequence of service and the executors’ efforts are regarded. Executors’ communications with other institutions and authorities are classified into hierarchical and non-hierarchical categories. Certain assumptions were made concerning the executioners’ geographical structure. The primary job of the executors is regarded, as it pertains to the implementation of rulings issued by the Kabardian Provisional Court and the head of the Caucasian Line Center. The executor’s attention is focused on the expenses of performing this feature. It is found that the line officials had a significant role in coordinating the executioners’ activity.